PERLINDUNGAN HUKUM BAGI PEKERJA ATAS PERMINTAAN IJAZAH ASLI OLEH PERUSAHAAN SEBAGAI JAMINAN - Dina Agustin; Dipo Wahjoeono (Gapenas Publisher, 2023)
Legal Protection is related to the way the government or authorities protect legal subjects with several existing rules, which are written or unwritten in legal instruments that have preventive or repressive properties. In East Java Provincial Regulation No.8 of 2016 Article 42 states that employers arek prohibited from holding or keeping the original documents of workers which are attached to workers as collateral. If based on these regulations companies (employers) should not request original documents, most of which are diplomas as a guarantee, moreover this is already prohibited and listed in a regional regulation, but it is very unfortunate that Manpower Act still does not regulate this matter. The workers are forced to agree to terms of the contract where usually the company makes a diploma a condition of the contract agreement, because they have no other choice. The problem is that when the contract agreement is completed and the workers ask for the diploma or document back, there are difficulties with the many reasons given by the company, while the workers have no debts or problem with the company. The author will dicuss efforts to protect the law against workers when the company ask for a certificate as collateral. The research method uses normative juridical approaches that are used are statutory and conceptual approaches. The result of the writing discussed th that workers get legal protection in accordance with applicable regulations